2016
DOI: 10.1186/s12916-016-0749-5
|View full text |Cite
|
Sign up to set email alerts
|

What works for whom in pharmacist-led smoking cessation support: realist review

Abstract: BackgroundNew models of primary care are needed to address funding and staffing pressures. We addressed the research question “what works for whom in what circumstances in relation to the role of community pharmacies in providing lifestyle interventions to support smoking cessation?”MethodsThis is a realist review conducted according to RAMESES standards. We began with a sample of 103 papers included in a quantitative review of community pharmacy intervention trials identified through systematic searching of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 75 publications
(158 reference statements)
0
48
0
Order By: Relevance
“…The main limitation of this review—in keeping with most realist reviews—is that the primary data often lacked sufficient detail about the interventions, or their context, and were largely atheoretical, making it difficult to produce robust CMO configurations . Indeed, the 12 mechanisms proposed in this review and the range of contextual factors identified should be considered as preliminary and in need of further empirical testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main limitation of this review—in keeping with most realist reviews—is that the primary data often lacked sufficient detail about the interventions, or their context, and were largely atheoretical, making it difficult to produce robust CMO configurations . Indeed, the 12 mechanisms proposed in this review and the range of contextual factors identified should be considered as preliminary and in need of further empirical testing.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as well as theoretical literature, this review could have extended its search to include a wider range of empirical literature from different clinical settings (eg, smoking, alcohol, domestic violence), which might have contributed to theory development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reviewed full-text articles to determine if they contained enough detail or theoretical discussion to contribute to our aims. 43 For transparency, we noted whether the relevance of contributions were high (well aligned to the review questions, with rich descriptions contributing to theory); moderate (some relevance to review question and some theoretical insights) or low (meets broad inclusion criteria and provides at least one insight).…”
Section: Refining the Review Focus With Stakeholdersmentioning
confidence: 99%
“…Realist evaluation is an established method in healthcare practice research, particularly for investigating the real-life implementation of interventions, guidelines or protocols. [26][27][28][29][30] The purpose of realist evaluation is to find out why interventions work differently across different contexts, 28,31 moving beyond a descriptive account to uncover deeper causal factors. 32 The aim of this evaluation was to explore: "does it work, for whom, when and why?"…”
Section: Materials S and Me Thodsmentioning
confidence: 99%